Removal of chromium (VI) from aqueous solution using vesicular basalt: A potential low cost wastewater treatment system. Issue 7 (July 2018) - Alemu, Agegnehu; Lemma, Brook; Gabbiye, Nigus; Alula, Melisew Tadele; Desta, Minyahl Teferi
Abstract: In this study, vesicular basalt volcanic rock was taken and its application for adsorption of chromium (VI) from aqueous solution was investigated. Different physical and chemical properties of the powdered rock was studied using Fourier transform infrared spectroscopy (FT-IR), Powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). A series of batch experiments were carried out to study the effect of various experimental parameters (pH, ionic strength and contact time) on chromium (VI) adsorption. It was found that the removal efficiency of chromium (VI) decreased with increasing pH and ionic strength. The adsorption process was optimal at pH 2. The maximum adsorption capacity was 79.20 mg kg −1 at an initial concentration of 5.0 mg L −1 and adsorbent dosage of 50 g L −1 . In individual adsorption tests, Pseudo-second-order kinetic and Freundlich isotherm models could better describe chromium (VI) adsorption on the vesicular basalt. This study indicated that vesicular basalt, which is inexpensive, has the potential to remove chromium (VI) from polluted water.